2021
DOI: 10.1186/s40463-021-00500-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular testing for cytologically suspicious and malignant (Bethesda V and VI) thyroid nodules to optimize the extent of surgical intervention: a retrospective chart review

Abstract: Background Molecular testing has been used for cytologically indeterminate thyroid nodules (Bethesda III and IV), where the risk of malignancy is 10–40%. However, to date, the role of molecular testing in cytologically suspicious or positive for malignancy (Bethesda V and VI) thyroid nodules has been controversial. The aim of this study was to determine whether patients who had molecular testing in Bethesda V and VI thyroid nodules had the optimal extent of surgery performed more often than pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Subsequently, another study was done to investigate if using the molecular testing preoperatively in the patients with Bethesda V and Bethesda VI thyroid nodules with no evidence of high-risk disease can optimize the extent of surgery. The study showed that 91.86% of the surgeries in the molecular group was optimal while it was only 61.11% in the group without the preoperative molecular testing [ 58 ]. This finding shows that using molecular testing in these patients decreases the chances of under or overtreatment from 38.89% to 8.14%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, another study was done to investigate if using the molecular testing preoperatively in the patients with Bethesda V and Bethesda VI thyroid nodules with no evidence of high-risk disease can optimize the extent of surgery. The study showed that 91.86% of the surgeries in the molecular group was optimal while it was only 61.11% in the group without the preoperative molecular testing [ 58 ]. This finding shows that using molecular testing in these patients decreases the chances of under or overtreatment from 38.89% to 8.14%.…”
Section: Discussionmentioning
confidence: 99%
“…The main outcome was to identify how many patients had the optimal surgery done when using molecular testing compared to patients without molecular testing (for example: if a lobectomy was the surgery planned and performed, no completion was necessary following final histopathological analysis). It was found that 91.86% of the patients in the molecular group had an optimal surgery while it was only 61.11% in the group without molecular testing [ 58 ]…”
Section: Clinical Utility and Our Group’s Experiencementioning
confidence: 99%
“…[7][8][9][10] Bethesda category V and VI nodules should continue to surgery; however, molecular testing of Bethesda category V and VI may lead to optimal primary surgery. 4,11 In summary, thyroid nodules >1.0 cm and reported as Bethesda category III and IV are recommended to undergo molecular testing, while molecular testing may be beneficial in Bethesda category V and VI in certain nodules. A flowchart summarizing the recommended clinical management of thyroid nodules via the Bethesda classification is included (Figure 1).…”
Section: The Bethesda System For Reporting Thyroid Cytopathologymentioning
confidence: 99%
“…180 The goal of molecular testing is to optimize patient management, by reducing unnecessary surgery on benign thyroid nodules and by resolving thyroid cytology diagnostic dilemmas; however, the field has evolved to include prognostic implications and clinical management of malignant nodules. 11,181 Hier et al found that patients with Bethesda V and VI nodules with molecular testing more often had optimal surgery defined as a total thyroidectomy in the presence of positive lymph node, extrathyroidal extension, or an aggressive pathological variant of PTC such as tall cell, hobnail, columnar cell, diffuse sclerosing, and solid/trabecular or a version of a subtotal thyroidectomy in all other cases as compared to Bethesda V and VI without molecular testing. 11 The National Comprehensive Cancer Network guidance recommends testing for select mutations in advanced thyroid cancer due to new treatments available to increase iodine sensitivity or other targeted therapy.…”
Section: Summary Of Molecular Assaysmentioning
confidence: 99%
See 1 more Smart Citation